Private equity, layoffs, and job polarization - Martin Olsson; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2015)
Although private equity firms are often criticized for layoffs, little evidence exists regarding which employees lose their jobs and why. We argue that explanations for the job polarization process can also explain layoffs after buyouts. Buyouts reduce agency problems, which triggers automation, offshoring, and tougher bargaining with labor unions. We show that workers in less productive firms who perform routine or offshorable job tasks are more likely to lose their jobs. The opposite trend holds for workers who perform non-routine or non-offshorable job tasks. Moreover, workers who belong to aggressive labor unions are more likely to lose their jobs.
Keywords: G32; G34; J60; 330; Employment; job polarization; labor unions; private equity buyouts; leveraged buyouts; offshoring; restructuring; task-biased technological change; unemployment